Bi‐Based Electrode Materials for Alkali Metal‐Ion Batteries. Issue 48 (5th November 2020) - Wang, Anni; Hong, Wanwan; Yang, Li; Tian, Ye; Qiu, Xuejing; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Alkali metal (Li, Na, K) ion batteries with high energy density are urgently required for large‐scale energy storage applications while the lack of advanced anode materials restricts their development. Recently, Bi‐based materials have been recognized as promising electrode candidates for alkali metal‐ion batteries due to their high volumetric capacity and suitable operating potential. Herein, the latest progress of Bi‐based electrode materials for alkali metal‐ion batteries is summarized, mainly focusing on synthesis strategies, structural features, storage mechanisms, and the corresponding electrochemical performance. Particularly, the optimization of electrode–electrolyte interphase is also discussed. In addition, the remaining challenges and further perspectives of Bi‐based electrode materials are outlined. This review aims to provide comprehensive knowledge of Bi‐based materials and offer a guideline toward more applications in high‐performance batteries. Abstract : In this review, latest progress of Bi‐based electrode materials (e.g., metallic Bi and its oxides, sulfides, alloys and other compounds) for alkali metal‐ion batteries is systematically summarized for the first time, mainly emphasizing on three aspects: storage mechanism, structural design, and optimization of electrode–electrolyte interface. Furthermore, the major challenges and perspectives are also pointed out.